Paperwork on legality and enforcement for experts meeting: Legalisation of cannabidiol products for medicinal use in Malaysia. - Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz (2022)
The term medical cannabis is not just a recent phenomenon but has long been introduced and used in the community. Many countries have legislatively amended cannabis from controlled to lesser regulated or unregulated substance groups – depending on the approved usage for either one, two, or all purposes of medical, recreational, and industrial purposes. It is not a surprise that cannabis was ranked as the most widely used substance worldwide. The prominent urge for legalisation in several countries is mainly due to industrial and economic pressure and, to a certain extent, for medical reasons. However, there are many issues reported from the legalizing countries, hence, the current legislation needs to be carefully scrutinized before any amendment is made so that in the long run, the later implementation will not produce any harm to the Malaysian population and the nation as a whole, especially to the young generations.